Pengaruh Religiusitas dan Moralitas Terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa (Studi Pada Desa di Kecamatan Ngoro dan Trawas Kabupaten Mojokerto) - Maulah, Lia Hikmatul; Mahsuni, Abdul Wahid; Amin, Moh. (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study goals to observe the impact of religiosity and morality on the prevention of fraud in handling village budget (a observe conducted in villages in the Ngoro and Trawas sub-districts, Mojokerto Regency). The sampling method used on these studies is purposive sampling. The populace includes the Village Head, Village Secretary, and Village Finance Head in Ngoro and Trawas sub-districts, Mojokerto Regency, East Java Province. Ngoro sub-district consists of 19 villages, while Trawas sub-district accommodates 13 villages. The consequences of the simultaneous check (F-check) suggest that the variables of religiosity and morality together have a large impact on fraud prevention in village fund control. The partial check results (t-take a look at) display that the religiosity variable has a nice and great effect on fraud prevention in village fund management. Further, the partial check effects (t-take a look at) display that the morality variable also has a fantastic and large impact on fraud prevention in village fund control.Keywords: Religiosity, Morality and Fraud Prevention